Income Effect and Environmental Sustainability in Nigeria - Enya Ndem, Bassey; Michael, Baghebor; Onyemaechi Kevin, Egesi, (International Journal of Scientific Research and Management (IJSRM), 2017)
This study “Effect of Income on Environmental Sustainability in Nigeria” is aimed at investigating whether sustainable environment is a major index of economic growth and to see if environmental sustainability affects economic growth; the study shall also establish whether Environmental Kuznets Curve exists in Nigeria. To achieve these, we have to check how the following variable per capita GDP affects the environmental factor Co2. The study then applied a simple regression analysis to test for the behavior of some variables. It was discovered that; environmental sustainability is a major indexes for sustainable development in Nigeria, On the other hand it was surprising to found that environmental degradation promote economic growth in Nigeria. The study also proved that there is the present of Environmental Kuznets Curve in Nigeria.